Mucocutaneous Histoplasmosis in immunocompetent adult patients (Bangladesh Journal of Medical Science, 2019)
Introduction: Histoplasmosis is a fungal infection caused by the agent Histoplasma capsulatum,a dimorphic fungus. The spectrum of illness ranges from subclinical infection to progressive disseminated disease. The major bulk of histoplasma infections are asymptomatic or pulmonary histoplasmosis. In immune compromised patients it can cause disseminated infections involving different organs of the body. In immune competent individuals it may cause isolated adrenal histoplasmosis.Material and methods: A retrospective study was done to look for mucocutaneous histoplasmosis. The excised tissue samples were cultured and only culture confirmed cases were included in the study.Result: Here, we present five cases of primary mucocutaneous histoplasmosis in immune competent individuals in a tertiary care centre in India. These patients had no other co-morbidities and had only isolated lesions in oral cavity or penis.The tissue on excision was cultured and showed growth of Histoplasma capsulatum. All the patients improved with treatment. There are limited cases of mucocutaneous ulcerated lesions caused by Histoplasma capsulatum in immune competent people in published literature.Conclusion: This study emphasizes the necessity of a vigilant look out and clinical suspicion of fungal causes like histoplasma in chronic non healing ulcers which should be confirmed by the laboratory investigations. Accurate diagnosis helps in specific management of these cases.Bangladesh Journal of Medical Science Vol.19(1) 2020 p.94-97